The virtual Sim(HU)lation model: Conceptualization and implementation in the context of distant learning in teacher education. (September 2022) - Frei-Landau, Rivi; Levin, Orna
Abstract: This paper presents a novel simulation model, developed amidst COVID-19, given the need to adapt the (ordinarily used) human-based clinical simulations to an online platform. The Virtual Sim(HU)lation (VSH) Model is a human-based virtual simulation. First, we conceptualize the model, its features and utilization, addressing the distance-learning-related challenges. Then, we present findings of a qualitative case study, reviewing the implementation of the VSH model in 37 workshops ( N  = 412). Analysis revealed three categories regarding the opportunities and obstacles of the VSH model. This study contributes to methodological, theoretical, and practical knowledge of designing online simulations for both routine and emergent use.